First record of introduction of metacarcinus magister dana, 1852 (Crustacea: Decapoda: Cancridae) and range extension of Eriocheir sinensis Milne-Edwards, 1853 (Crustacea: Decapoda: Varunidae) in the long Island sound - Hudson, D.M.; Schaefer-Padgett, S.; Christie, B.L.; Harris, R. (BioInvasions Records, 2019)
Invasive crustacean species have been present in the Long Island Sound, northwestern Atlantic Ocean, for over two centuries. Three new records of introduction are recorded here from collections by local fishermen. Two records are for male Dungeness crabs, Metacarcinus magister (Dana, 1852), collected in the Western Long Island Sound (2017) and Cape Cod Bay (2018). The other record is that of a range extension documented by a single male Chinese mitten crab, Eriocheir sinensis (Milne-Edwards, 1853), found in New Haven Harbor, Connecticut. Both species could potentially harbor nonnative epibionts and endoparasites. Additionally, E. sinensis may be more likely to establish, as it has in numerous locations in the region and worldwide. © Hudson et al.
0 citations (Crossref) [2023-10-31]
Keywords: Brachyura; Chinese mitten crab; Connecticut; Dungeness crab; Introduced species; Invasive species; Massachusetts; dept.bio; peer-reviewed

The mid-network mayfly maxima (MMM): A general pattern of mayfly (Ephemeroptera) species richness within drainage networks and what we can learn from it - Burian, Steven K. (Zoosymposia, 2019)
For the last 93 years mayfly diversity has been studied at all taxonomic levels from families to populations and all spatial and temporal scales. This has resulted in the description of almost every possible pattern with regard to latitude, elevation, habitat, climate, and season. However, if the focus is on species and sampling restricted to nymphs and the spatial scale limited to drainage networks, then a single recurring pattern appears—the hump-shaped Mid-network Mayfly Maxima (MMM). Past studies have attempted to explain this hump-shaped pattern with regards to some combination of ecologic, hydrologic, climatic, anthropogenic, or historic variables. There is wide agreement that some of these variables are important to the occurrence and distribution of individual species, but there is no consensus as to what combination of these variables comprises the best general explanation of the humped-shaped pattern. Because of the lack of agreement on how to explain this recurring pattern for mayflies and an unwillingness to acknowledge it as a general feature of drainage networks, where mayflies occur, we have become stuck trying to tease out a cause and have failed to recognize that although knowing a cause is important it may not be relevant to the broader use of this information for biomonitoring, climate monitoring, habitat management, and conservation now. I believe that there is sufficient evidence that the MMM exists and occurs in almost every major drainage system and is reasonably predictable using basic attributes of drainage networks pertinent to the aquatic life stage (nymphs). Herein I will summarize pertinent studies that support this contention; reexamine some results from one of the most comprehensive recent studies that included mayfly taxa along altitudinal gradients in North America by Gill et al. (2014), as well as a test dataset from a river in western Maine, USA; comment on information needed to estimate the location of MMM in any drainage network and how the MMM can be used; and discuss how the extent of common vs. rare species affect the perceptions of the regional species pool and the MMM.
Number: 1
Keywords: Ephemeroptera; Mayfly; dept.bio; peer-reviewed; ⚠️ Invalid DOI

So You Want to Start an Institutional Biosafety Committee - Schniederberend, Maren; Fontes, Benjamin; Jeffrey, Rachel (Applied Biosafety, 2019)
Introduction: The number of institutions engaging in research with potentially biohazardous materials has increased, indicating a need for newly formed Institutional Biosafety Committees (IBCs) in the United States and for similar biorisk management committees located outside the United States. Our institution identified the need for an IBC due to the growth of pertinent activities on campus. Objectives: This article shares our experiences creating a new IBC at our institution from September 2017 to April 2019. Our lessons learned and approaches to the challenges faced may be helpful to others finding themselves with similar needs. Methods: In this case study, we outline IBC membership, documents, relationships with federal agencies and within the institution, creation of registration forms, and the review process. Along with our account, we have included links to helpful resources from federal agencies. Results: At the time of the submission of this article, we have established our IBC and reviewed two registrations. Conclusion: This case report demonstrates the successful creation of an IBC that works for our current institutional needs. © ABSA International 2019.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/177-624-967-404-713, pop00102 tex.type: [object Object]
Keywords: BMBL; EHS; IBC; NIH Guidelines; biorisk management; dept.bio; peer-reviewed; standard operating procedure

Ephemeroptera - Burian, Steven K. (An introduction to the aquatic insects of North America, 2019)
"As with previous editions, this new one is intended to serve as a standard guide to the aquatic and semiaquatic insects of North America"–Preface, xi.
Google-Books-ID: nLh_yAEACAAJ
Keywords: dept.bio; faculty_collection

Understanding maladaptation by uniting ecological and evolutionary perspectives - Brady, Steven P.; Bolnick, Daniel I.; Barrett, Rowan D. H.; Chapman, Lauren; Crispo, Erika; Derry, Alison M.; Eckert, Christopher G.; Fraser, Dylan J.; Fussmann, Gregor F.; Gonzalez, Andrew; Guichard, Frederic; Lamy, Thomas; et al. (The American Naturalist, 2019)
Evolutionary biologists have long trained their sights on adaptation, focusing on the power of natural selection to produce relative fitness advantages while often ignoring changes in absolute fitness. Ecologists generally have taken a different tack, focusing on changes in abundance and ranges that reflect absolute fitness while often ignoring relative fitness. Uniting these perspectives, we articulate various causes of relative and absolute maladaptation and review numerous examples of their occurrence. This review indicates that maladaptation is reasonably common from both perspectives, yet often in contrasting ways. That is, maladaptation can appear strong from a relative fitness perspective, yet populations can be growing in abundance. Conversely, resident individuals can appear locally adapted (relative to nonresident individuals) yet be declining in abundance. Understanding and interpreting these disconnects between relative and absolute maladaptation, as well as the cases of agreement, is increasingly critical in the face of accelerating human-mediated environmental change. We therefore present a framework for studying maladaptation, focusing in particular on the relationship between absolute and relative fitness, thereby drawing together evolutionary and ecological perspectives. The unification of these ecological and evolutionary perspectives has the potential to bring together previously disjunct research areas while addressing key conceptual issues and specific practical problems. © 2019 by The University of Chicago. All rights reserved.
54 citations (Crossref) [2023-10-31]
Keywords: Adaptation; Fitness; Global change; Maladaptation; adult; article; dept.bio; drawing; ecologist; environmental change; female; global change; human; human experiment; male; natural selection; peer-reviewed; resident

Causes of maladaptation. - Brady, Steven P; Bolnick, Daniel I; Angert, Amy L; Gonzalez, Andrew; Barrett, Rowan D H; Crispo, Erika; Derry, Alison M; Eckert, Christopher G; Fraser, Dylan J; Fussmann, Gregor F; Guichard, Frederic; Lamy, Thomas; et al. (Evolutionary applications, 2019)
Evolutionary biologists tend to approach the study of the natural world within a framework of adaptation, inspired perhaps by the power of natural selection to produce fitness advantages that drive population persistence and biological diversity. In contrast, evolution has rarely been studied through the lens of adaptation's complement, maladaptation. This contrast is surprising because maladaptation is a prevalent feature of evolution: population trait values are rarely distributed optimally; local populations often have lower fitness than imported ones; populations decline; and local and global extinctions are common. Yet we lack a general framework for understanding maladaptation; for instance in terms of distribution, severity, and dynamics. Similar uncertainties apply to the causes of maladaptation. We suggest that incorporating maladaptation-based perspectives into evolutionary biology would facilitate better understanding of the natural world. Approaches within a maladaptation framework might be especially profitable in applied evolution contexts - where reductions in fitness are common. Toward advancing a more balanced study of evolution, here we present a conceptual framework describing causes of maladaptation. As the introductory article for a Special Feature on maladaptation, we also summarize the studies in this Issue, highlighting the causes of maladaptation in each study. We hope that our framework and the papers in this Special Issue will help catalyze the study of maladaptation in applied evolution, supporting greater understanding of evolutionary dynamics in our rapidly changing world.
79 citations (Crossref) [2023-10-31] Place: England Brady, Steven P. Biology Department Southern Connecticut State University New Haven CT USA. Bolnick, Daniel I. Department of Ecology and Evolutionary Biology University of Connecticut Mansfield CT USA. Angert, Amy L. Departments of Botany and Zoology University of British Columbia Vancouver BC Canada. Gonzalez, Andrew. Department of Biology McGill University Montreal QC Canada. Gonzalez, Andrew. Quebec Centre for Biodiversity Science, Stewart Biology McGill University Montreal QC Canada. Barrett, Rowan D H. Department of Biology McGill University Montreal QC Canada. Barrett, Rowan D H. Quebec Centre for Biodiversity Science, Stewart Biology McGill University Montreal QC Canada. Barrett, Rowan D H. Redpath Museum McGill University Montreal QC Canada. Crispo, Erika. Department of Biology Pace University New York NY USA. Derry, Alison M. Quebec Centre for Biodiversity Science, Stewart Biology McGill University Montreal QC Canada. Derry, Alison M. Departement des sciences biologiques Universite du Quebec a Montreal Montreal QC Canada. Eckert, Christopher G. Department of Biology Queen's University Kingston ON Canada. Fraser, Dylan J. Department of Biology Concordia University Montreal QC Canada. Fussmann, Gregor F. Department of Biology McGill University Montreal QC Canada. Fussmann, Gregor F. Quebec Centre for Biodiversity Science, Stewart Biology McGill University Montreal QC Canada. Guichard, Frederic. Department of Biology McGill University Montreal QC Canada. Guichard, Frederic. Quebec Centre for Biodiversity Science, Stewart Biology McGill University Montreal QC Canada. Lamy, Thomas. Departement de sciences biologiques Universite de Montreal Montreal QC Canada. Lamy, Thomas. Marine Science Institute University of California Santa Barbara CA USA. McAdam, Andrew G. Department of Integrative Biology University of Guelph Guelph ON Canada. Newman, Amy E M. Department of Integrative Biology University of Guelph Guelph ON Canada. Paccard, Antoine. McGill University Genome Center Montreal QC Canada. Rolshausen, Gregor. Senckenberg Biodiversity and Climate Research Centre (SBiK-F) Frankfurt am Main Germany. Simons, Andrew M. Department of Biology Carleton University Ottawa ON Canada. Hendry, Andrew P. Department of Biology McGill University Montreal QC Canada. Hendry, Andrew P. Quebec Centre for Biodiversity Science, Stewart Biology McGill University Montreal QC Canada. Hendry, Andrew P. Redpath Museum McGill University Montreal QC Canada.
Keywords: adaptation; dept.bio; fitness; global change; maladaptation; peer-reviewed

Fundamental and applied pursuits in evolutionary toxicology are mutually beneficial: A reply to Hahn (2018). - Brady, Steven P; Monosson, Emily; Matson, Cole; Bickham, John W (Evolutionary applications, 2019)
0 citations (Crossref) [2023-10-31] Place: England Brady, Steven P. Biology Department Southern Connecticut State University New Haven CT USA. Monosson, Emily. Ronin Institute for Independent Scholars, Department of Environmental Conservation University of Massachusetts Amherst MA USA. Matson, Cole. Department of Environmental Science and Center for Reservoir and Aquatic Systems Research (CRASR) Baylor University Waco TX USA. Bickham, John W. Department of Wildlife & Fisheries Sciences Texas A&M University College Station TX USA.
Keywords: Evolutionary toxicology; contemporary evolution; dept.bio; ecotoxicology; peer-reviewed

Fitter frogs from polluted ponds: The complex impacts of human-altered environments - Brady, Steven P.; Zamora‐Camacho, Francisco J.; Eriksson, Fredrik A. A.; Goedert, Debora; Comas, Mar; Calsbeek, Ryan (Evolutionary Applications, 2019)
Human-modified habitats rarely yield outcomes that are aligned with conservation ideals. Landscapes that are subdivided by roads are no exception, precipitating negative impacts on populations due to fragmentation, pollution, and road kill. Although many populations in human-modified habitats show evidence for local adaptation, rarely does environmental change yield outright benefits for populations of conservation interest. Contrary to expectations, we report surprising benefits experienced by amphibian populations breeding and dwelling in proximity to roads. We show that roadside populations of the wood frog, Rana sylvatica, exhibit better locomotor performance and higher measures of traits related to fitness compared with frogs from less disturbed environments located further away from roads. These results contrast previous evidence for maladaptation in roadside populations of wood frogs studied elsewhere. Our results indicate that altered habitats might not be unequivocally detrimental and at times might contribute to metapopulation success. While the frequency of such beneficial outcomes remains unknown, their occurrence underscores the complexity of inferring consequences of environmental change.
15 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/025-521-919-587-494, pop00127 tex.type: [object Object]
Keywords: amphibian; dept.bio; human-modified habitats; maladaptation; peer-reviewed; road salt; roads

Immunofluorescence and image analysis pipeline for Drosophila motor neurons - Brown, Jeremy R; Brown, Jeremy R; Phongthachit, Chanpasith; Sulkowski, Mikolaj J (Biology Methods and Protocols, 2019)
The neuromuscular junction (NMJ) of larval Drosophila is widely used as a genetic model for basic neuroscience research. The presynaptic side of the NMJ is formed by axon terminals of motor neurons, the soma of which reside in the ventral ganglion of the central nervous system (CNS). Here we describe a streamlined protocol for dissection and immunostaining of the Drosophila CNS and NMJ that allows processing of multiple genotypes within a single staining tube. We also present a computer script called Automated Image Analysis with Background Subtraction which facilitates identification of motor nuclei, quantification of pixel intensity, and background subtraction. Together, these techniques provide a pipeline for neuroscientists to compare levels of different biomolecules in motor nuclei. We conclude that these methods should be adaptable to a variety of different cell and tissue types for the improvement of efficiency, reproducibility, and throughput during data quantification. © 2019 The Author(s) 2019. Published by Oxford University Press.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/072-055-143-711-580 tex.type: [object Object]
Keywords: dept.bio; peer-reviewed

Is it time to begin prenatal/neonatal screening for autism risk? - Crawford, Sarah Adelaide (Global Journal of Pediatrics & Neonatal Care, 2019)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/111-162-730-836-405, pop00188
Keywords: dept.bio; peer-reviewed

Conservation through the lens of (mal)adaptation: Concepts and meta-analysis - Derry, Alison Margaret; Fraser, Dylan J.; Brady, Steven P.; Astorg, Louis; Lawrence, Elizabeth R.; Martin, Gillian K.; Matte, Jean-Michel; Dastis, Jorge Octavio Negrín; Paccard, Antoine; Barrett, Rowan D. H.; Chapman, Lauren J.; Lane, Jeffrey E.; et al. (Evolutionary Applications, 2019)
Evolutionary approaches are gaining popularity in conservation science, with diverse strategies applied in efforts to support adaptive population outcomes. Yet conservation strategies differ in the type of adaptive outcomes they promote as conservation goals. For instance, strategies based on genetic or demographic rescue implicitly target adaptive population states whereas strategies utilizing transgenerational plasticity or evolutionary rescue implicitly target adaptive processes. These two goals are somewhat polar: adaptive state strategies optimize current population fitness, which should reduce phenotypic and/or genetic variance, reducing adaptability in changing or uncertain environments; adaptive process strategies increase genetic variance, causing maladaptation in the short term, but increase adaptability over the long term. Maladaptation refers to suboptimal population fitness, adaptation refers to optimal population fitness, and (mal)adaptation refers to the continuum of fitness variation from maladaptation to adaptation. Here, we present a conceptual classification for conservation that implicitly considers (mal)adaptation in the short-term and long-term outcomes of conservation strategies. We describe cases of how (mal)adaptation is implicated in traditional conservation strategies, as well as strategies that have potential as a conservation tool but are relatively underutilized. We use a meta-analysis of a small number of available studies to evaluate whether the different conservation strategies employed are better suited toward increasing population fitness across multiple generations. We found weakly increasing adaptation over time for transgenerational plasticity, genetic rescue, and evolutionary rescue. Demographic rescue was generally maladaptive, both immediately after conservation intervention and after several generations. Interspecific hybridization was adaptive only in the F1 generation, but then rapidly leads to maladaptation. Management decisions that are made to support the process of adaptation must adequately account for (mal)adaptation as a potential outcome and even as a tool to bolster adaptive capacity to changing conditions.
41 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/005-301-824-151-444, pop00098 tex.type: [object Object]
Keywords: adaptation; demographic rescue; dept.bio; evolutionary rescue; gene flow; genetic rescue; hybridization; peer-reviewed; transgenerational plasticity; translocation

Ecological feedbacks stabilize a turf-dominated ecosystem at the southern extent of kelp forests in the Northwest Atlantic. - Feehan, Colette J; Grace, Sean P; Narvaez, Carla A (Scientific reports, 2019)
Temperate marine ecosystems globally are undergoing regime shifts from dominance by habitat-forming kelps to dominance by opportunistic algal turfs. While the environmental drivers of shifts to turf are generally well-documented, the feedback mechanisms that stabilize novel turf-dominated ecosystems remain poorly resolved. Here, we document a decline of kelp Saccharina latissima between 1980 and 2018 at sites at the southernmost extent of kelp forests in the Northwest Atlantic and their replacement by algal turf. We examined the drivers of a shift to turf and feedback mechanisms that stabilize turf reefs. Kelp replacement by turf was linked to a significant multi-decadal increase in sea temperature above an upper thermal threshold for kelp survival. In the turf-dominated ecosystem, 45% of S. latissima were attached to algal turf rather than rocky substrate due to preemption of space. Turf-attached kelp required significantly (2 to 4 times) less force to detach from the substrate, with an attendant pattern of lower survival following 2 major wave events as compared to rock-attached kelp. Turf-attached kelp allocated a significantly greater percentage of their biomass to the anchoring structure (holdfast), with a consequent energetic trade-off of slower growth. The results indicate a shift in community dominance from kelp to turf driven by thermal stress and stabilized by ecological feedbacks of lower survival and slower growth of kelp recruited to turf.
24 citations (Crossref) [2023-10-31] Place: England Feehan, Colette J. Department of Biology, Montclair State University, Montclair, NJ, 07043, USA. feehanc@montclair.edu. Grace, Sean P. Department of Biology and Werth Center for Coastal and Marine Studies, Southern Connecticut State University, New Haven, CT, 06515, USA. Narvaez, Carla A. Department of Biology, Villanova University, Villanova, PA, 19085, USA.
Keywords: *Forests; *Kelp/ph [Physiology]; *Marine Biology/mt [Methods]; *Seawater; Atlantic Ocean; Bays; Biomass; Climate Change; Forests; Kelp; Kelp/gd [Growth & Development]; Marine Biology; Rhode Island; Seasons; Seawater; Temperature; article; bay; biomass; climate change; dept.bio; driver; feedback system; forest; growth; development and aging; human; kelp; marine biology; physiology; procedures; sea water; season; temperature; temperature stress

Fitness attributes of bacterial and fungal seed endophytes of tall fescue - Roberts, Elizabeth Lewis; Mormile, Brendan; Adamchek, Christopher (Seed Endophytes: Biology and Biotechnology, 2019)
Increased fitness in tall fescue (Festuca arundinacea) is attributed to infection by Epichloë coenophiala. However, plant growth-promoting (PGP) bacteria also increase the fitness of many host plants, and PGP bacteria have been shown to dominate the phyllosphere and rhizosphere microbiome of E. coenophiala-infected (E+) tall fescue. Because E. coenophialum lives endophytically in tall fescue seeds, we hypothesized that PGP bacteria also live within the seeds and could provide fitness advantages to the host. Endophyte-infected (E+) and endophyte-free (E−) Kentucky-31 tall fescue seeds were surface sterilized to remove epiphytic bacteria. Surface sterilized and non-surface sterilized control plants of each type were cultivated for 6 weeks before withholding water to simulate drought. Normal watering was resumed after 4 days. Plant recovery of each group was measured by assigning a numerical value to tillers based on the state of decline. Surface-sterilized E+ plants were unable to recover as efficiently as E+ controls but outperformed both E− groups. Additionally, total 16S amplified DNA extracted from each seed type was analyzed with Illumina sequencing to assess the internal microbial communities from E+ and E− seeds as well as the seed coat microbiome. E+ seeds have lower diversity of endophytic bacterial species and are dominated by Pseudomonadaceae. Further, several of the seed endophytes are PGP bacterial strains.
Citation Key Alias: lens.org/004-523-831-959-190
Keywords: Clavicipitaceae; Epichloë coenophialum; Epichloë spp.; Plant growth promotion; Plant growth-promoting bacteria; Plant growthpromoting bacteria; Stress tolerance; Tall fescue; dept.bio

Colonization of the tsetse fly midgut with commensal Kosakonia cowanii Zambiae inhibits trypanosome infection establishment. - Weiss, Brian L; Maltz, Michele A; Vigneron, Aurelien; Wu, Yineng; Walter, Katharine S; O'Neill, Michelle B; Wang, Jingwen; Aksoy, Serap (PLOS Pathogens, 2019)
Tsetse flies (Glossina spp.) vector pathogenic trypanosomes (Trypanosoma spp.) in sub-Saharan Africa. These parasites cause human and animal African trypanosomiases, which are debilitating diseases that inflict an enormous socio-economic burden on inhabitants of endemic regions. Current disease control strategies rely primarily on treating infected animals and reducing tsetse population densities. However, relevant programs are costly, labor intensive and difficult to sustain. As such, novel strategies aimed at reducing tsetse vector competence require development. Herein we investigated whether Kosakonia cowanii Zambiae (Kco_Z), which confers Anopheles gambiae with resistance to Plasmodium, is able to colonize tsetse and induce a trypanosome refractory phenotype in the fly. Kco_Z established stable infections in tsetse's gut and exhibited no adverse effect on the fly's survival. Flies with established Kco_Z infections in their gut were significantly more refractory to infection with two distinct trypanosome species (T. congolense, 6% infection; T. brucei, 32% infection) than were age-matched flies that did not house the exogenous bacterium (T. congolense, 36% infected; T. brucei, 70% infected). Additionally, 52% of Kco_Z colonized tsetse survived infection with entomopathogenic Serratia marcescens, compared with only 9% of their wild-type counterparts. These parasite and pathogen refractory phenotypes result from the fact that Kco_Z acidifies tsetse's midgut environment, which inhibits trypanosome and Serratia growth and thus infection establishment. Finally, we determined that Kco_Z infection does not impact the fecundity of male or female tsetse, nor the ability of male flies to compete with their wild-type counterparts for mates. We propose that Kco_Z could be used as one component of an integrated strategy aimed at reducing the ability of tsetse to transmit pathogenic trypanosomes.
28 citations (Crossref) [2023-10-31] Place: United States Weiss, Brian L. Yale School of Public Health, Department of Epidemiology of Microbial Diseases, New Haven, Connecticut, United States of America. Maltz, Michele A. Southern Connecticut State University, New Haven, Connecticut, United States of America. Vigneron, Aurelien. Yale School of Public Health, Department of Epidemiology of Microbial Diseases, New Haven, Connecticut, United States of America. Wu, Yineng. Yale School of Public Health, Department of Epidemiology of Microbial Diseases, New Haven, Connecticut, United States of America. Walter, Katharine S. Yale School of Public Health, Department of Epidemiology of Microbial Diseases, New Haven, Connecticut, United States of America. O'Neill, Michelle B. Yale School of Public Health, Department of Epidemiology of Microbial Diseases, New Haven, Connecticut, United States of America. Wang, Jingwen. Yale School of Public Health, Department of Epidemiology of Microbial Diseases, New Haven, Connecticut, United States of America. Aksoy, Serap. Yale School of Public Health, Department of Epidemiology of Microbial Diseases, New Haven, Connecticut, United States of America. Erratum in (EIN)
Keywords: *Trypanosoma brucei brucei/py [Pathogenicity]; *Trypanosoma congolense/py [Pathogenicity]; *Trypanosomiasis; African/pc [Prevention & Control]; *Tsetse Flies/mi [Microbiology]; *Tsetse Flies/ps [Parasitology]; Adult; Africa South of the Sahara; Africa south of the Sahara; African trypanosomiasis; Animals; Anopheles; Anopheles gambiae; Anopheles/mi [Microbiology]; Article; Drosophila; Enterobacteriaceae; Female; Glossinidae; Humans; Male; Mosquito Vectors; Mosquito Vectors/mi [Microbiology]; Mosquito Vectors/ps [Parasitology]; Plasmodium; Serratia infection; Symbiosis; Trypanosoma brucei brucei; Trypanosoma congolense; Trypanosomiasis; African; Trypanosomiasis; African/me [Metabolism]; Trypanosomiasis; African/mi [Microbiology]; Trypanosomiasis; African/ps [Parasitology]; Tsetse Flies; adult; animal; animal experiment; animal model; animal tissue; antibacterial activity; ascorbic acid; bacterial load; blood flow; cell proliferation assay; clinical effectiveness; colony forming unit; controlled study; cysteine; dept.bio; disease predisposition; economics; female; fitness; fluorescence; genotype phenotype correlation; health program; human; immune system; male; metabolism; microbial colonization; microbiology; microscopy; mosquito vector; nonhuman; pH; parasitology; pathogenicity; peer-reviewed; peptidoglycan recognition protein; population; probability; semen analysis; survival analysis; symbiosis; trypanosomiasis